Method for preparing zinc-rich epoxy powder coating with high adhesive force
By using modified graphene and nano-cerium phytate in epoxy zinc-rich coatings, the conductive paths and optimized coating structure are formed, and the coating problem caused by excessive zinc powder content is solved, and the corrosion resistance and adhesion are improved. The efficient utilization of zinc powder and the excellent performance of coating are achieved.
Patent Information
- Application Number
- CN202411408001.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-10
AI Technical Summary
In harsh corrosive environments such as the ocean, excessive zinc powder content in epoxy zinc-rich coatings leads to sedimentation of zinc powder and hole defects, reducing the mechanical properties of the coating. The best choice and amount of existing graphene in the coating are not clear. , affects corrosion resistance.
Modified graphene is used to form a conductive path between zinc powder particles. By combining Ti3C2 and ZrP, graphene is grafted together, the amount of zinc powder is reduced, the utilization rate of zinc powder is increased, and bio-based nano cerium phytate is added as a corrosion inhibitor. , optimize the coating structure to enhance corrosion resistance.
It significantly improves the corrosion resistance and adhesion of the coating, extends the cathode protection time, enhances the density and tensile strength of the coating, optimizes the utilization rate of zinc powder and the shielding effect of the coating, compared with the individual The coating performance of graphene modified with Ti3C2 or ZrP is better.
Smart Images

Figure BDA0005077209680000071 
Figure BDA0005077209680000081 
Figure BDA0005077209680000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, in particular to a method for preparing a zinc-rich epoxy powder coating with high adhesion. Background Art
[0002] Epoxy zinc-rich coatings have the advantages of hard coatings, good adhesion to metals, and are widely used in heavy-duty anti-corrosion fields such as bridges, ships, buildings, and pipelines. The zinc powder content in epoxy zinc-rich coatings varies according to the requirements of different anti-corrosion levels. In harsh corrosive environments such as marine environments, the zinc powder content needs to be greater than 50wt%, but excessive zinc powder content will cause serious zinc powder sedimentation in the zinc-rich coating, resulting in more hole defects in the coating and reducing the mechanical properties of the coating. Improving the anti-corrosion performance of epoxy zinc-rich coatings while reducing the content of zinc powder in epoxy zinc-rich coatings has important practical significance and research value.
[0003] There have been many studies on the application of graphene in epoxy zinc-rich coatings. Existing literature shows that the corrosion resistance of solvent-based epoxy zinc-rich primers is greatly improved after adding graphene, and the neutral salt spray resistance time can reach up to 4000h. However, it is still unclear what kind of graphene to choose, the optimal addition amount, and the corrosion resistance mechanism of graphene in the coating. Selecting the appropriate type of graphene, optimizing the addition amount of graphene, and preparing epoxy zinc-rich primers with stable and excellent anti-corrosion performance have always been the focus of scholars' research. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a zinc-rich epoxy powder coating with high adhesion, using modified graphene to form a conductive path between zinc powder particles, reducing the amount of zinc powder used, and improving the overall utilization rate of the zinc powder in the coating. At the same time, a good shielding effect is formed to block the penetration of corrosive media and enhance the anti-corrosion performance of the coating.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] A method for preparing a zinc-rich epoxy powder coating with high adhesion, wherein the zinc-rich epoxy powder coating is composed of a component A and a component B; wherein the component A is prepared from the following components in mass fractions: 70-80% of epoxy resin, 1-15% of modified graphene, 2-12% of water and 0.4-2% of auxiliary agent A; and the component B is prepared from the following components in mass fractions: 3-10% of epoxy curing agent, 15-50% of zinc powder, 10-30% of super phosphorus zinc white, 1-3% of sericite, 3-15% of propylene glycol methyl ether acetate, 0.1-0.5% of bentonite, 1-5% of corrosion inhibitor and 0.6-3.0% of auxiliary agent B;
[0007] The preparation method of the zinc-rich epoxy powder coating comprises the following steps:
[0008] S1, preparation of modified graphene;
[0009] S2, weighing the raw material components of component A except the phenolic curing agent according to the ratio, mixing them and dispersing them evenly using a disperser, then adding the phenolic curing agent and continuing to stir and disperse, and grinding and sieving again to obtain component A;
[0010] S3, weighing the raw material components of component B according to the proportion, dispersing and shearing and mixing them evenly by a disperser, and then grinding and sieving the mixed materials to obtain component B.
[0011] Preferably, the auxiliary agent A comprises 0.1-0.5% of a defoamer, 0.1-0.5% of a wetting agent, 0.1-0.5% of a thickener, and 0.1-0.5% of an anti-flash rust agent.
[0012] Preferably, the auxiliary agent B includes 0.5-2.0% dispersant, 0.1-0.5% defoamer, and 0.1-0.3% leveling agent.
[0013] Preferably, the corrosion inhibitor is bio-based nano-cerium phytate.
[0014] Preferably, the specific method for preparing modified graphene in step S1 is as follows:
[0015] S11, using plasma-assisted high-energy ball milling equipment, expanded graphite, Ti 3 C 2、 , ZrP and oleic acid solution were ultrasonically mixed and then placed in a tank for plasma-assisted high-energy ball milling, and primary powder was obtained after ball milling for 10 hours;
[0016] S12, treating the primary powder prepared in step S11 with petroleum ether as an extractant, repeatedly centrifuging until the upper petroleum ether solution after extraction is clear and transparent, and taking the precipitate;
[0017] S13, taking the precipitate in step S12, placing it in a drying oven at 90° C. and drying it for 30-40 min to prepare a powder to obtain modified graphene.
[0018] Preferably, the ball milling conditions in step S11 are: the discharge voltage is 22 kV, the vibration frequency of the ball mill is 16 Hz, the amplitude is 10 mm, and the ball mill is in an atmospheric environment of 0.1 MPa.
[0019] Preferably, the specific method for preparing component A in step S2 is as follows:
[0020] S21, mixing solid epoxy resin, defoamer, wetting agent and anti-rust agent, and then dispersing the mixture evenly at a speed of 1000 r / min using a disperser to obtain a mixed material 1;
[0021] S22, adding the thickener to the phenolic curing agent, heating to 140-180° C. and stirring evenly, adding the molten material to the mixed material 1 obtained in step S21, and continuing to heat and disperse for 30 minutes to obtain the mixed material 2;
[0022] S23, adding graphene to the mixed material 2 obtained in step S22, adjusting the speed of the disperser to 1800r / min and continuing the dispersion and shearing for 30min, transferring the mixture to the screw extruder for extrusion, tableting, and crushing to obtain a preliminarily solidified powder, then taking it out, grinding it again with a grinder, and sieving it to obtain component A.
[0023] Preferably, the specific method for preparing component B in step S3 is as follows:
[0024] S31, mixing epoxy curing agent, defoaming agent, dispersant, leveling agent and propylene glycol methyl ether acetate, and then uniformly dispersing the mixture using a disperser at 1000 r / min to obtain a mixed material 3;
[0025] S32, adding bentonite to the mixture 3 obtained in step S31, stirring for 60 minutes to obtain a mixture 4;
[0026] S33, adding sericite, super phosphorus zinc white and zinc powder to the mixed material 4 obtained in step S32 in sequence, stirring for 30 minutes, to obtain a mixed material 5;
[0027] S34, adding the corrosion inhibitor to the mixed material 5 obtained in step S33, stirring evenly, pouring into a sand mill, grinding at 2000 r / min for 30 min, and sieving to obtain component B.
[0028] Beneficial effects of the present invention:
[0029] 1. The present invention adopts modified graphene to add epoxy zinc-rich primer to improve the shielding performance of the coating, prolong its cathodic protection time, and enhance the corrosion resistance of the coating; the covalent grafting method is used to modify the graphene, which reduces the aggregation of graphene oxide flakes in the epoxy matrix, and can greatly increase the concentration and stability of the graphene dispersion, thereby enhancing the density and adhesion of the coating.
[0030] 2. The present invention adopts Ti 3 C 2、 By grafting graphene with ZrP, the modified graphene can have strong corrosion resistance while still having excellent tensile strength and thermal stability. The modified graphene is then used to form a conductive path between zinc powder particles, reducing the amount of zinc powder used and increasing the overall utilization rate of zinc powder in the coating. At the same time, it forms a good shielding effect, blocks the penetration of corrosive media, enhances the corrosion resistance of the coating, and helps improve adhesion.
[0031] 3. The present invention also adds bio-based nano-cerium phytate as a corrosion inhibitor, which is evenly dispersed in the epoxy zinc-rich coating to form a new protective film on the surface of the substrate to assist in enhancing the corrosion resistance. DETAILED DESCRIPTION
[0032] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.
[0033] Solid epoxy resin 604 (industrial grade): Jinan Baorui Resin Chemical Co., Ltd.; polyamide curing agent, phenolic amine curing agent, fatty amine curing agent (industrial grade): Guangdong Tongde Co., Ltd.; propylene glycol methyl ether acetate (industrial grade): Xinchuan Chemical Co., Ltd.; thickener (industrial grade), anti-flash rust agent (industrial grade): Tianjin Shangde Xinjia Co., Ltd.; dispersant, defoamer, wetting agent, leveling agent are all industrial grade: Efcona Polymer Co., Ltd.; zinc powder (industrial grade): Jiangsu Shenlong Zinc Industry Co., Ltd.; ferrophosphorus powder (industrial grade), super phosphorus zinc white (industrial grade): Henan Huijin Co., Ltd.; sericite (industrial grade): Anhui Ge Rui Co., Ltd.; bentonite (industrial grade): Zhejiang Hongyu Co., Ltd.; expanded graphite: Suzhou Ge Ruifeng Nano Technology Co., Ltd.; oleic acid: Shandong Jubang Chemical Co., Ltd.; Ti 3 C 2 , ZrP: Beijing Zhongke Leiming Technology Co., Ltd.
[0034] Example 1
[0035] Preparation of modified graphene:
[0036] Using plasma-assisted high-energy ball milling equipment, 1g expanded graphite, 3g Ti 3 C 2 , 2g ZrP and 500ml oleic acid solution were ultrasonically mixed and then placed in a tank for plasma-assisted high-energy ball milling. The ball milling conditions were: discharge voltage of 22kV, ball mill vibration frequency of 16Hz, amplitude of 10mm, and 0.1MPa atmospheric environment of the ball mill. Primary powder was obtained after ball milling for 10h; the prepared primary powder was treated with petroleum ether as an extractant, and centrifuged repeatedly until the upper petroleum ether solution after extraction was clear and transparent, and the precipitate was taken; the precipitate was placed in a drying oven and dried at 90°C for 30-40min to obtain a powder to obtain modified graphene.
[0037] Example 2
[0038] Preparation of Component A:
[0039] 100 g of solid epoxy resin, 0.3 g of defoamer, 0.2 g of wetting agent and 0.2 g of anti-flash rust agent were mixed and dispersed evenly in a disperser at a speed of 1000 r / min to obtain mixed material 1; 0.4 g of thickener was added to 6.8 g of phenolic curing agent, heated to 158°C and stirred evenly, and then added to mixed material 1 after forming a molten substance, and continued to heat and disperse for 30 minutes to obtain mixed material 2; graphene was added to mixed material 2, the speed of the disperser was adjusted to 1800 r / min, and the dispersion and shearing were continued for 30 minutes, and the mixture was transferred to a screw extruder for extrusion, tableting, and crushing to obtain a preliminarily cured powder, which was then taken out and ground again by a grinder and sieved to obtain component A.
[0040] The addition amounts of modified graphene were 1 g, 2 g, 4 g, 6 g, 8 g, 10 g, 12 g, and 14 g, respectively, to prepare components A1-A8.
[0041] Example 3
[0042] Preparation of component B:
[0043] 8 g of epoxy curing agent, 1.2 g of defoaming agent, 0.3 g of dispersant, 0.2 g of leveling agent, and 9.8 g of propylene glycol methyl ether acetate were mixed and uniformly dispersed using a disperser at 1000 r / min to obtain a mixed material 3;
[0044] 0.4 g of bentonite was added to the mixture 3 and stirred for 60 min to obtain the mixture 4;
[0045] 2.5 g of sericite, 18 g of super phosphorus zinc white and zinc powder were added to the mixture 4 in sequence, and stirred for 30 min to obtain the mixture 5;
[0046] 4 g of corrosion inhibitor was added to the mixed material 5, and after being stirred evenly, the mixture was poured into a sand mill and ground at 2000 r / min for 30 min. Component B was obtained by sieving.
[0047] The added amounts of zinc powder were 15 g, 20 g, 25 g, 30 g, 35 g, 40 g, 45 g and 50 g, respectively, to prepare components B1-B8.
[0048] Example 4
[0049] Components A1-A8 were combined with components B1-B8 to prepare zinc-rich epoxy powder coatings. The combinations are shown in Table 1 below.
[0050] Component A and component B were mixed in a mass ratio of 13:1 and stirred evenly. After ripening, the coating was applied twice with an interval of 24 hours between each coating. The coating was cured in a constant temperature and humidity chamber at 25°C and 50% relative humidity for 7 days before testing.
[0051] Table 1 Coating formula
[0052] coating Component A1 Component A2 Component A3 Component A4 Component A5 Component A6 Component A7 Component A8 Component B1 1 2 3 4 5 6 7 8 Component B2 9 10 11 12 13 14 15 16 Component B3 17 18 19 20 21 22 23 24 Component B4 25 26 27 28 29 30 31 32 Component B5 33 34 35 36 37 38 39 40 Component B6 41 42 43 44 45 46 47 48 Component B7 49 59 51 52 53 54 55 56 Component B8 57 58 59 60 61 62 63 64
[0053] Example 5
[0054] The viscosity of the coating was measured according to GB / T 9269-2009 “Determination of coating viscosity - Stormer viscometer method”.
[0055] The coating's appearance and drying time, bendability, impact resistance and other performance tests are all conducted by applying the coating on a 120mm×50mm×(0.2-0.3)mm tinplate, and the cross-cut test is conducted on a 150mm×75mm×(0.45-0.55)mm steel plate. Except for the drying time test, all tests require 48 hours of curing, and the dry film thickness is (25±3)μm. The coating's drying time test refers to GB / T1728–2020 "Determination of Drying Time of Paint Film and Putty Film", the coating's bending test refers to GB / T 6742–2007 "Bending Test for Paints and Varnishes (Cylindrical Shaft)", and the impact resistance test refers to GB / T 1732–2020 "Determination of Impact Resistance of Paint Film".
[0056] The pull-off adhesion test of the coating was conducted using a PosiTest AT pull-off tester in accordance with GB / T5210-2006 "Pull-off adhesion test for paints and varnishes", with a coating dry film thickness of (45±5)μm. The test substrate was a sandblasted steel plate of 150mm×75mm×(3-5)mm, and the substrate was pretreated in accordance with the requirements of Clause 4.3.1 of the chemical industry standard HG / T 4564-2013 "Epoxy coatings with low surface treatment tolerance".
[0057] The coating for corrosion resistance test is coated on a steel plate which has been sandblasted to Sa 2.5 level as specified in GB / T 8923.1-2011 "Surface preparation of steel before coating - Visual assessment of surface cleanliness - Part 1: Rust grades and treatment grades for uncoated steel surfaces and steel surfaces after complete removal of existing coatings". The size of the steel plate is 150 mm × 75 mm × (3-5) mm.
[0058] The alkali resistance of the coating (i.e. the time required for the coating to be damaged in a 50g / L NaOH solution) is tested according to the immersion method in GB / T9274-1988 "Determination of resistance of paints and varnishes to liquid media", and the dry film thickness of the coating is (45±5)μm. The sample is cured in a constant temperature room at (23±2)℃ for 7 days and then tested according to relevant standards.
[0059] The salt spray resistance of the coating (i.e., the time required for the coating to be damaged in a 50g / L neutral salt spray test) is tested in a Q-FOG salt spray test chamber according to GB / T1771-2007 "Determination of neutral salt spray resistance of paints and varnishes", and the dry film thickness of the coating is (90±10)μm.
[0060] The test results are shown in Table 2 below.
[0061] Table 2 Effect of different amounts of modified graphene and zinc powder on coating properties
[0062]
[0063]
[0064]
[0065] From the above test results, it can be seen that when the amount of modified graphene is between 6%-10% and the amount of zinc powder is between 35%-40%, the performance test results of zinc-rich epoxy powder coating are relatively excellent. While ensuring high adhesion, it can also achieve excellent corrosion resistance and flexibility, and the overall performance is the best.
[0066] Example 6
[0067] According to the test results of Example 5, formula A5xB4 was selected, and the amount of modified graphene was 8 g and the amount of zinc powder was 30 g as Test Example 1 of the present invention. A comparative example was prepared, and modified graphene was prepared according to the method of Example 1:
[0068] Using plasma-assisted high-energy ball milling equipment, 1g expanded graphite, 5g Ti 3 C 2 After being evenly mixed with 500 ml of oleic acid solution by ultrasonication, the mixture was placed in a tank for plasma-assisted high-energy ball milling. The ball milling conditions were as follows: the discharge voltage was 22 kV, the vibration frequency of the ball mill was 16 Hz, the amplitude was 10 mm, and the ball mill tank was in an atmospheric environment of 0.1 MPa. Primary powder was obtained after ball milling for 10 hours. The prepared primary powder was treated with petroleum ether as an extractant, and the mixture was repeatedly centrifuged until the upper petroleum ether solution was clear and transparent after extraction, and the precipitate was taken. The precipitate was placed in a drying oven and dried at 90°C for 30-40 minutes to obtain a powder to obtain modified graphene 1.
[0069] Using plasma-assisted high-energy ball milling equipment, 1g of expanded graphite, 5g of ZrP and 500ml of oleic acid solution were ultrasonically mixed and then placed in a tank for plasma-assisted high-energy ball milling. The ball milling conditions were: the discharge voltage was 22kV, the vibration frequency of the ball mill was 16Hz, the amplitude was 10mm, and the ball mill tank was in an atmospheric environment of 0.1MPa. After ball milling for 10h, primary powder was obtained; the prepared primary powder was treated with petroleum ether as an extractant, and centrifuged repeatedly until the upper petroleum ether solution after extraction was clear and transparent, and the precipitate was taken; the precipitate was placed in a drying oven at 90°C and dried for 30-40min to obtain a powder to obtain modified graphene 2.
[0070] The above-mentioned modified graphene 1 and modified graphene 2 were respectively used to replace the modified graphene in component A5 and then combined with component B4 to prepare comparative test examples 1 and 2 of the coating. The existing product thermal spray zinc coating (purchased from Shaanxi Kemanchen New Materials Technology Co., Ltd.) was selected as comparative example 3, and the modified graphene in component A5 was removed and then combined with component B4 to prepare comparative test example 4 of the coating, and then a performance comparison test was carried out.
[0071] The test results are shown in Table 3.
[0072] Table 3 Performance test of different coatings
[0073]
[0074] From the above test results, it can be seen that the present invention adopts Ti 3 C 2、 Grafting graphene with ZrP can make the modified graphene have strong corrosion resistance while still having excellent tensile strength and thermal stability. Then the modified graphene is used to form a conductive path between zinc powder particles, reducing the amount of zinc powder, improving the overall utilization rate of zinc powder in the coating, and forming a good shielding effect to block the penetration of corrosive media, enhance the corrosion resistance of the coating, and help improve adhesion. Compared with using Ti alone, 3 C 2、 Or a coating of ZrP modified graphene, the coating prepared by using the two together has better performance. Compared with the existing thermal spray zinc coating with excellent performance, the coating performance test results of the present invention are also better.
[0075] All technical features in this embodiment can be modified in appearance according to actual needs.
[0076] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present technical solution is within the protection scope of the present invention.
Claims
1. A method for preparing a high-adhesion zinc-rich epoxy powder coating, characterized in that: The zinc-rich epoxy powder coating is composed of component A and component B; Wherein, component A is prepared from the following components in mass fractions: 70-80% of epoxy resin, 1-15% of modified graphene, 6-12% of phenolic curing agent and 0.4-2% of auxiliary agent A; Component B is prepared from the following components in mass fractions: 3-10% epoxy curing agent, 15-50% zinc powder, 10-30% super phosphorus zinc white, 1-3% sericite, 3-15% propylene glycol methyl ether acetate, 0.1-0.5% bentonite, 1-5% corrosion inhibitor and 0.6-3.0% additive B; The preparation method of the zinc-rich epoxy powder coating comprises the following steps: S1, preparation of modified graphene; S2, weighing the raw material components of component A except the phenolic curing agent according to the ratio, mixing them and dispersing them evenly using a disperser, then adding the phenolic curing agent and continuing to stir and disperse, and grinding and sieving again to obtain component A; S3, weighing the raw material components of component B according to the ratio, dispersing and shearing and mixing them evenly by a disperser, and then grinding and sieving the mixed materials to obtain component B.
2. The method for preparing a high-adhesion zinc-rich epoxy powder coating according to claim 1, characterized in that: The auxiliary agent A comprises 0.1-0.5% of a defoamer, 0.1-0.5% of a wetting agent, 0.1-0.5% of a thickener, and 0.1-0.5% of an anti-flash rust agent.
3. The method for preparing a high-adhesion zinc-rich epoxy powder coating according to claim 1, characterized in that: The auxiliary agent B includes 0.5-2.0% of a dispersant, 0.1-0.5% of a defoamer, and 0.1-0.3% of a leveling agent.
4. The method for preparing a high-adhesion zinc-rich epoxy powder coating according to claim 1, characterized in that: The corrosion inhibitor is bio-based nano-cerium phytate.
5. The method for preparing a high-adhesion zinc-rich epoxy powder coating according to any one of claims 1 to 4, characterized in that: The specific method for preparing modified graphene in step S1 is as follows: S11, using plasma-assisted high-energy ball milling equipment, expanded graphite, Ti3C 2、 , ZrP and oleic acid solution were ultrasonically mixed and then placed in a tank for plasma-assisted high-energy ball milling, and primary powder was obtained after ball milling for 10 hours; S12, treating the primary powder prepared in step S11 with petroleum ether as an extractant, repeatedly centrifuging until the upper petroleum ether solution after extraction is clear and transparent, and taking the precipitate; S13, taking the precipitate in step S12, placing it in a drying oven at 90° C. and drying it for 30-40 min to prepare a powder to obtain modified graphene.
6. The method for preparing a high-adhesion zinc-rich epoxy powder coating according to claim 5, characterized in that: The ball milling conditions in step S11 are as follows: the discharge voltage is 22 kV, the vibration frequency of the ball mill is 16 Hz, the amplitude is 10 mm, and the ball milling tank is in an atmospheric environment of 0.1 MPa.
7. The method for preparing a high-adhesion zinc-rich epoxy powder coating according to any one of claims 1 to 4, characterized in that: The specific method for preparing component A in step S2 is as follows: S21, mixing solid epoxy resin, defoamer, wetting agent and anti-rust agent, and then dispersing the mixture evenly at a speed of 1000 r / min using a disperser to obtain a mixed material 1; S22, adding the thickener to the phenolic curing agent, heating to 140-180° C. and stirring evenly, adding the molten material to the mixed material 1 obtained in step S21, and continuing to heat and disperse for 30 minutes to obtain the mixed material 2; S23, adding graphene to the mixed material 2 obtained in step S22, adjusting the speed of the disperser to 1800r / min and continuing the dispersion and shearing for 30min, transferring the mixture to the screw extruder for extrusion, tableting, and crushing to obtain a preliminarily solidified powder, then taking it out, grinding it again with a grinder, and sieving it to obtain component A.
8. The method for preparing a high-adhesion zinc-rich epoxy powder coating according to any one of claims 1 to 4, characterized in that: The specific method for preparing component B in step S3 is as follows: S31, mixing epoxy curing agent, defoaming agent, dispersant, leveling agent and propylene glycol methyl ether acetate, and then dispersing the mixture uniformly at 1000 r / min using a disperser to obtain a mixed material 3; S32, adding bentonite to the mixture 3 obtained in step S31, stirring for 60 minutes to obtain a mixture 4; S33, adding sericite, super phosphorus zinc white and zinc powder to the mixed material 4 obtained in step S32 in sequence, stirring for 30 minutes, to obtain a mixed material 5; S34, adding the corrosion inhibitor to the mixed material 5 obtained in step S33, stirring evenly, pouring into a sand mill, grinding at 2000 r / min for 30 min, and sieving to obtain component B.
Citation Information
Patent Citations
Epoxy zinc-rich coating for highway guardrails and preparation method thereof
CN111777924A
Graphene epoxy-based corrosion-resistant base powder and preparation method thereof
CN113563785A
Anticorrosive paint applied to petroleum pipeline and preparation method of anticorrosive paint
CN115368806A
High-weather-resistance metal powder coating and preparation method thereof
CN118291010A